INNOVATIVE APPROACHES TO ENTERPRISE MANAGEMENT EMPLOYING ADVANCED COMPUTER TECHNOLOGIES - Viktoria M. Krivosheeva; Irina V. Zaitseva (Вестник Северо-Кавказского федерального университета)
In a highly competitive environment in the service sector, successful operation for an organization is possible only if the latter employs computer technologies to improve the quality of its customer service. The winner here is the one that is able to offer the clients the full range of services in the shortest time possible. The paper describes a subsystem developed in order to improve and facilitate the work done by an employee making it much faster if compared to the conventional paperwork in accounting; it also allows the user to quickly extract the data required. The elements of this subsystem are used for effective management of the enterprise.